(untitled) (Research, Society and Development, 2024)
Introduction: Schizophrenia can be considered a chronic syndrome with multifactorial and heterogeneous causes, as well as genetic predisposition and psychosocial factors. It presents itself through distortion of reality through delusions, hallucinations, poverty of content, loosening of associations and even catatonia. Objective: To analyze the occupational performance of patients diagnosed with Schizophrenia treated at a Psychiatry Outpatient Clinic through Occupations. Methods: This is a descriptive study, using a qualitative approach, in which the study subjects were 10 (ten) users of a Psychiatry Outpatient Clinic at a University Hospital Discussion and results: Through the patients’ statements, it was possible to find a routine restricted to everyday activities, without functional and/or occupational repertoire in other environments in which the individual is inserted, causing social isolation and loss of functionality. Final considerations: In view of the discussion, the importance of working with users on their occupations is clear, creating a greater functional repertoire and daily activities, in order to work on their autonomy and independence.